Peran Kedokteran Forensik dalam Pengungkapan Kasus Tindak Pidanan Kekerasan Seksual di Provinsi Kep. Bangka Belitung: Penelitian - Wahyu Hidayati Dwi Palupi; Arista Candra Irawati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the role and obstacles of forensic medicine in the process of uncovering and proving sexual violence crimes in the Bangka Belitung Islands Province. This study uses an empirical legal method with a socio-legal approach, where primary data is obtained through interviews and observations of forensic examinations under the coordination of the Medical and Health Division (Biddokkes) of the Bangka Belitung Islands Regional Police, while secondary data is obtained from literature studies, laws and regulations, and previous research results. The results of the study show that forensic medicine plays an important role in providing objective scientific evidence through the preparation of autopsy reports, DNA testing, and biological analysis to strengthen the evidence process in court. However, the effectiveness of forensic medicine still faces various obstacles, such as the limited number of forensic experts, the unavailability of regional forensic laboratories, delays in sending samples to the National Police Headquarters' Forensic Laboratory, and ethical and psychological constraints of victims who refuse to undergo medical examinations. From a theoretical perspective, these findings reinforce Lawrence M. Friedman's view on the effectiveness of law, whereby weaknesses in the legal structure can reduce the overall quality of law enforcement.